2019
DOI: 10.2478/jee-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

The influence of substrate bias voltage on the electrochemical properties of ZrN thin films deposited by radio-frequency magnetron sputtering: Biomedical application

Abstract: In order to study the influence of the substrate bias on the properties of ZrN thin films deposited by radio-frequency magnetron sputtering for biomedical application. Films of ZrN were grown onto 316L stainless steel substrate using radio-frequency (rf) magnetron sputtering from a pure zirconium target in Ar - N2 gas mixture. The substrate bias voltage was varied from 0 to −100 V, which produces a variation in the structural and electrochemical properties of the obtained films. The deposited films were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This technology has the potential to achieve very high quality ZrN thin films that could be deposited on non-planar substrates and is promising for a wide range of applications in which the ZrN is used e.g. biomedical applications [56,57], decorative and protective coatings [58] and as a diffusion barrier in microelectronics [59] The possibility of structuring the layers opens the way for other…”
Section: Discussionmentioning
confidence: 99%
“…This technology has the potential to achieve very high quality ZrN thin films that could be deposited on non-planar substrates and is promising for a wide range of applications in which the ZrN is used e.g. biomedical applications [56,57], decorative and protective coatings [58] and as a diffusion barrier in microelectronics [59] The possibility of structuring the layers opens the way for other…”
Section: Discussionmentioning
confidence: 99%
“…The high crystalline quality of the film, which has an effect on the corrosion resistance, is one of the most important characteristics of the coatings, which can be improved by using the appropriate deposition procedure. Corrosion resistance of ZrN films can be improved by changing the coating parameters [ 40–44 ] and the PVD processes are widely used for deposition of ZrN coating with better corrosion resistance than other methods. However, there is no investigation and understanding of the effect of nitrogen percentage on the corrosion behavior, in hank's solution, of stainless steel AISI 316L coated with Zr‐N by radio frequency magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that uniform and crystalline Zr x N y thin films could be fabricated by sputtering on biodegradable metals and alloys, [ 30 ] and furthermore, the films were improved by substrate biasing. [ 31 ] The correlation between the concentration of N vacancies versus the corrosion resistance of Zr x N y films was deliberated by Pei et al [ 32 ] A relatively high content of 0.3 vacancies provided the lowest corrosion rate. Furthermore, the lowered processing pressure enhanced the hardness and corrosion inhibition as well as nitrogen vacancy incorporation.…”
Section: Introductionmentioning
confidence: 99%